NÚMEROS PRIMOS E A CRIPTOGRAFIA RSA - Molinari, José Robyson Aggio (2016)
This study presents some of the encryption methods used in antiquity as well as the advance in the way of encrypting. The main objective of this work is the study of RSA Method: its Historical context, the importance of prime numbers, the inefficiency of factorization algorithms, coding, decoding, its security and a study of the Euler function. Some activities with mathematical content related to encryption have been developed. Thus, it is expected that this research can present an auxiliary methodology for teaching certain math content, linked to the utilization of cryptography.